Історична матриця “руський мир” та однойменний сучасний пропагандистський міф країни-агресорки: до деконструкції концепту - Верховцева, Ірина Геннадіївна (Протидія дезінформації в умовах російської агресії проти України: виклики і перспективи: тези доп. учасників міжн. наук.-практ. конф. (Анн-Арбор - Харків, 12-13 груд. 2023 р.), 2023)
The deconstruction of the concept of “Russian world” is carried out on the basis of the actualization of the historical matrix “Russian world” associated with the traditional self-governing practices of the Great Russian provinces of the Russian Empire in the rural self-government of the “long” XIX century. The scientific study of the role of the Russian world in the unification (“bonding”) processes on the vast expanses of this state proves that it turned from a tool of empire building and colonization of enslaved peoples into a factor in the destruction of this state, the cradle of Russian fascism. Therefore, the modern version of the concept “Russian world” is a banal simulacrum and a tool of information manipulation.